A survey report on the ITM Sarawak mentor- mentee program: What the mentees say / Lucila Ang Abey ... [et al.]. - Abey, Lucila Ang; Low, Kuek Long (Institut Teknologi Mara Cawangan Sarawak, 1990)
A committee comprising of lecturers and administrative officers within the Institut Teknologi MARA, Sarawak Branch Campus was formed under the chairmanship of Encik Abdul Rahman Deen, Deputy Principal, Student Affairs. The Committee set out to study the relevance-effectiveness of the Mentor-Mentee Program (MMP) re-introduced in this campus in July 1987. The reporters are members of the investigating team who specifically study the case based on the mentees' responses to a questionnaire survey.